2019
DOI: 10.1016/j.ynstr.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Shared gray matter reductions across alcohol use disorder and posttraumatic stress disorder in the anterior cingulate cortex: A dual meta-analysis

Abstract: The considerable comorbidity of posttraumatic stress disorder (PTSD) and alcohol use disorders (AUD) poses a greater public health burden than either condition alone. Although there is a substantial body of evidence linking the direct neurotoxic effect of heavy drinking to gray matter (GM) deficits, as well as a growing body of literature supporting a strong association between PTSD and GM alterations, there is scant research interrogating the direct interaction of the two disorders. In order to generate data-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 148 publications
1
28
0
Order By: Relevance
“…Several reasons might account for these differences. First, the applied methodology: Xiao et al 26 , Yang et al 27 and Klaming et al 28 used effect size based methods (ES-SDM and AES-DM, e.g. 69 ), which makes their strategy different from to the ALE analysis used here.…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons might account for these differences. First, the applied methodology: Xiao et al 26 , Yang et al 27 and Klaming et al 28 used effect size based methods (ES-SDM and AES-DM, e.g. 69 ), which makes their strategy different from to the ALE analysis used here.…”
Section: Discussionmentioning
confidence: 99%
“…Using the lipidomic analytical approaches, we revealed that some species belonging to GPs were significantly altered in both PFC and striatum of alcohol-exposed rats. GPs are the key components of membrane structure and their composition vary a lot among different cell types, organelles, and inner/outer membranes in mammalian mitochondria due to their divergent biological functions (De et al 2018;Klaming et al 2019). As GPs provide neural membranes with stability, fluidity and permeability, they are required for normal biological function of integral…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, stress-enhanced fear learning (SEFL) in rats exposed to infant or adult trauma has been used as a preclinical model of posttraumatic stress disorder (PTSD) 23,26 . PTSD and AUD exhibit significant comorbidity in clinical populations, suggesting that the neural substrates mediating vulnerability for these two disorders may be similar [27][28][29][30][31] . While acute stress does increase rodent alcohol consumption in some studies, results are inconsistent 20,32 .…”
mentioning
confidence: 99%